The Prevalence, Associated Factors, and Clinical Characterization of Malassezia folliculitis in Patients Clinically Diagnosed with Acne Vulgaris - Paichitrojjana A; Chalermchai T (Dove Medical Press, 2022)
Anon Paichitrojjana, Thep Chalermchai School of Anti-Aging and Regenerative Medicine, Mae Fah Luang University, Bangkok, ThailandCorrespondence: Thep Chalermchai, School of Anti-Aging and Regenerative Medicine, Mae Fah Luang University, 36/87-88 PS Tower 25fl, Asoke Road, Sukhumvit 21, Klong Toey Nua, Wattana, Bangkok, 10110, Thailand, Tel +66-2-6644360, Email thep_chalermchai@hotmail.comBackground: The clinical presentation of Malassezia folliculitis (MF) can imitate acne vulgaris (AV), making it difficult to distinguish between the two conditions. Moreover, MF can coexist with AV in the same patient. The incidence of MF in patients clinically diagnosed with AV may be underestimated. This study aimed to determine the prevalence, associated factors, and clinical characterization of MF patients diagnosed with AV.Materials and Methods: Three hundred twenty new acne patients were questioned regarding general information, including age, sex, itchy symptoms, and past treatment history with antibiotics and steroids within four weeks. Clinical presentations of AV (location and severity), dandruff, and seborrheic dermatitis were examined by a dermatologist. Cytologic studies to determine the abnormal proliferation of Malassezia yeasts were performed from pustules or, in the absence of pustules, comedo-like papules, and comedones. The smears were stained with methylene blue and evaluated under a light microscope by the researcher.Results: The prevalence of MF in patients clinically diagnosed with AV was 28.8% (95% Confidence interval: CI = 23.8% - 33.7%), which can be classified as 24.7% were AV with MF and the remaining 4.1% were MF only. This study revealed that patients diagnosed with MF were 7.38 times more likely to have itchy symptoms than patients diagnosed with AV. MF patients had 8.89 times and 9.17 times higher risk of acneiform lesions on the scalp/ hairline and upper back than those who did not have MF, respectively.Conclusion: This present study revealed a high prevalence of MF in patients clinically diagnosed with AV. Dermatologists should be aware of MF when encountering AV patients with acneiform lesions on the scalp/ hairline and upper back with pruritus. Diagnosis based on clinical presentations alone may lead to misdiagnosis. Methylene blue staining is easy to perform and beneficial to diagnose MF.Keywords: Malassezia folliculitis, Pityrosporum folliculitis, acne vulgaris, methylene blue, yeast